Innovative good practices for using ICT in the classroom. - Baldaque, Alexandra (2014)
In the recent years there has been, at European level, an increase in the implementation of Information and Communication Technologies (ICT) in Education, due to different strategies and policies implemented in several projects since the 80s. In the literature much has been debated about the potential of ICT and its applications in Education. It discusses and problematizes how ICT can help to extend or renew the traditional means of knowledge production bearing in mind that they allow access to multiple opportunities for interaction, mediation and expression, facilitated by flows of information and operational flexibility [1]; [2]. The reality we see in primary and secondary schools leads us to realize that the ICT measures recommended by government in schools are not being fully implemented, at least effectively between students and teachers. In this way, the main proposal of this investigation is to draw a roadmap of the implementation/use of ICT in Primary and Secondary Schools in order to assess their use and thus design guidelines in order to find best practices of ICT use in teaching-learning processes. In particular, the study and design focus on the application of ICT in sciences teaching and learning. This paper will characterize some innovative good practices for using ICT in the classroom for Maths and ICT teaching programs we have found in our research and we can recommend to disseminate in other countries over the world.